Erythropoietin production by the kidney and the liver in response to severe hypoxia evaluated by Western blotting with deglycosylation. Issue 12 (26th June 2020) - Yasuoka, Yukiko; Fukuyama, Takashi; Izumi, Yuichiro; Nakayama, Yushi; Inoue, Hideki; Yanagita, Kengo; Oshima, Tomomi; Yamazaki, Taiga; Uematsu, Takayuki; Kobayashi, Noritada; Shimada, Yoshitaka; Nagaba, Yasushi; et al.
Abstract: The detection of erythropoietin (Epo) protein by Western blotting has required pre‐purification of the sample. We developed a new Western blot method to detect plasma and urinary Epo using deglycosylation. Epo in urine and tissue, and erythropoiesis‐stimulating agents (ESAs) in urine were directly detected by our Western blotting. Plasma Epo and ESAs were not detected by direct application but were detected by our Western blotting after deglycosylation. The broad bands of Epo and ESAs were shifted to 22 kDa by deglycosylation except for PEG‐bound epoetin β pegol. The 22 kDa band from an anemic patient's urine was confirmed by Liquid Chromatography/Mass Spectrometry (LC/MS) to contain human Epo. Severe hypoxia (7% O2, 4 hr) caused a 400‐fold increase in deglycosylated Epo expression in rat kidneys, which is consistent with the increases in both Epo gene expression and plasma Epo concentration. Immunohistochemistry showed Epo expression in nephrons but not in interstitial cells under control conditions, and hypoxia increased Epo expression in interstitial cells but not in tubules. These data show that intrinsic Epo and all ESAs can be detected by Western blot either directly in urine or after deglycosylation in blood, and that the kidney but not the liver is the main site of Epo production in control and severe hypoxia. Our method will make the tests for Epo doping and detection easy. Abstract : The glycosylated Epo production by the kidney in response to severe hypoxia increased by 10–20 times. Deglycosylated Epo production by the kidney showed 400‐fold increase by severe hypoxia.